Advancing Sustainable Development Goals (SDGs) through Blockchain-Enhanced Halal Supply Chains in Indonesia and Malaysia - Moch. Mahsun; Mahamadaree Waeno (Majapahit Journal of Islamic Finance and Management, 2025)
Integrating blockchain technology in the halal supply chain presents a transformative approach to enhancing transparency, efficiency, and compliance with halal certification standards. This study conducts a comparative policy analysis between Indonesia and Malaysia, examining the regulatory frameworks, technological readiness, and strategic adoption models influencing blockchain implementation. Using a mixed-method approach, we employ SOAR (Strengths, Opportunities, Aspirations, Results) analysis to identify key drivers and potential growth areas and QSPM (Quantitative Strategic Planning Matrix) to evaluate strategic alternatives for blockchain adoption. Our findings highlight that Indonesia focuses on strengthening halal certification transparency, whereas Malaysia has progressed further in integrating blockchain within logistics and international halal trade. While both countries recognize blockchain’s potential in achieving SDG 9 (Industry, Innovation, and Infrastructure), SDG 10 (Reduced Inequality), and SDG 12 (Responsible Consumption and Production), challenges remain in technological accessibility, regulatory standardization, and industry-wide adoption. The study recommends a hybrid approach, combining national blockchain adoption to enhance certification integrity with regional collaboration to standardize halal blockchain frameworks globally. This research contributes to the ongoing discourse on blockchain’s role in sustainable supply chain management and provides actionable insights for policymakers, industry leaders, and halal certification bodies.